Understanding social entrepreneurship : the relentless pursuit of mission in an ever changing world - Kickul, Jill R.; Lyons, Thomas S. (2020)
"Understanding Social Entrepreneurship is the leading textbook that provides students with a comprehensive overview of the field. It brings the mindset, principles, strategies, tools, and techniques of entrepreneurship into the social sector to present innovative solutions to today's vexing social issues. Kickul and Lyons cover all the key topics relevant to social entrepreneurship, including a detailed examination of each of the steps in the entrepreneurial process. This third edition includes several new features: A process-oriented format, taking students through discovery, design, development, and delivery Two new chapters: one on lean startup and design thinking for social entrepreneurship, and another on unconventional approaches from developing countries Updated and new case studies, with improved global coverage "Practically Speaking" sections that explore evidence-based research from the field Bringing together a rigorous theoretical foundation and a strong practical focus, this is the go-to resource for students of social entrepreneurship at undergraduate and postgraduate levels. A companion website includes an instructor's manual, PowerPoint slides, test bank, and other tools to provide additional support for students and instructors"--
Revised edition of the authors' Understanding social entrepreneurship, 2016.
Includes bibliographical references and index.
Keywords: Social entrepreneurship